1996
DOI: 10.1111/j.1539-6924.1996.tb01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the Link Between Global Climate Change and Predicted Health Risks from Pollution: Hexachlorobenzene (HCB) Case Study Using a Fugacity Model

Abstract: Industrial societies have altered the earth's environment in ways that could have important, longterm ecological, economic, and health implications. In this paper, we examine the extent to which uncertainty about global climate change could impact the precision of predictions of secondary outcomes such as health impacts of pollution. Using a model that links global climate change with predictions of chemical exposure and human health risk in the Western region of the United States of America (U.S.), we define … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Qian et al (2008) found a synergistic effect of PM 10 and high temperatures on daily cardio-respiratory (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007a;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006) ▪ The elderly and individuals with pre-existing cardio-respiratory disease may be more vulnerable to these effects Altered exposure and risk ▪ Some populations may experience increases or decreases in POP exposures and health risks depending on the region and diet of exposed individuals (Bard, 1999;Gordon, 1997;McKone et al, 1996;Watkinson et al, 2003) ▪ Pesticides may impair mechanisms of temperature regulation especially during times of thermal stress Increased susceptibility to pathogens ▪ Toxicants can suppress immune function, and climate-induced shifts in disease vector range will result in novel pathogen exposure (Abadin et al, 2007;Haines et al, 2006;Lipp et al, 2002;Nagayama et al, 2007;Patz et al, 2005;Rogers and Randolph, 2000;Smialowicz et al, 2001) ▪ Immune system impairment linked to toxicants may increase human vulnerability to climate shifts in pathogens ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible exposures may sensitize individuals to allergic disease ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible mortality in Wuhan, China. The PM 10 effects were strongest on extremely high temperature days (daily average temperature 33.1°C) and weakest during normal temperature days (daily average temperature 18°C).…”
Section: Air Pollutants and Cardio-respiratory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Qian et al (2008) found a synergistic effect of PM 10 and high temperatures on daily cardio-respiratory (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007a;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006) ▪ The elderly and individuals with pre-existing cardio-respiratory disease may be more vulnerable to these effects Altered exposure and risk ▪ Some populations may experience increases or decreases in POP exposures and health risks depending on the region and diet of exposed individuals (Bard, 1999;Gordon, 1997;McKone et al, 1996;Watkinson et al, 2003) ▪ Pesticides may impair mechanisms of temperature regulation especially during times of thermal stress Increased susceptibility to pathogens ▪ Toxicants can suppress immune function, and climate-induced shifts in disease vector range will result in novel pathogen exposure (Abadin et al, 2007;Haines et al, 2006;Lipp et al, 2002;Nagayama et al, 2007;Patz et al, 2005;Rogers and Randolph, 2000;Smialowicz et al, 2001) ▪ Immune system impairment linked to toxicants may increase human vulnerability to climate shifts in pathogens ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible exposures may sensitize individuals to allergic disease ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible mortality in Wuhan, China. The PM 10 effects were strongest on extremely high temperature days (daily average temperature 33.1°C) and weakest during normal temperature days (daily average temperature 18°C).…”
Section: Air Pollutants and Cardio-respiratory Diseasementioning
confidence: 99%
“…McKone et al (1996) conducted a study to model the effects of a 5°C increase in temperature on human health risks in western U.S. populations exposed to HCB. Their analysis concluded that this global warming scenario would have little negative impact on health risk associated with HCB among these populations.…”
Section: Altered Effects Of Pops and Pesticidesmentioning
confidence: 99%
“…In principle, the effect on solvent switching by a 5 ˚C temperature rise, for example, can be predicted by temperature coefficients for phase partitioning. Modeling suggests that temperature changes of this order are likely to lead to only small changes in risk, and probably reduced risk as increased temperature drives contaminants out of the water or off surfaces (25). In contrast, solvent depletion processes are sensitive to the projected changes and probably offer greater opportunity for surprises.…”
Section: Onto Global Changementioning
confidence: 99%
“…Several attempts have also been made to use computer models to project the impact of GCC on the fate and bioaccumulation of chemicals in future scenarios 1219. In many instances, the reviews and modeling studies have focused on the Arctic and on either persistent organic pollutants (POPs) or mercury 6, 10, 11.…”
mentioning
confidence: 99%